The effect of various types and doses of statins on C-reactive protein levels in patients with dyslipidemia or coronary heart disease: A systematic review and network meta-analysis - Zhang, Jie; Wang, Xinyi; Tian, Wende; Wang, Tongxin; Jia, Jundi; Lai, Runmin; Wang, Tong; Zhang, Zihao; Song, Luxia; Ju, Jianqing; Xu, Hao (Frontiers in Cardiovascular Medicine, 2022)
Objective: To measure the efficacy of various types and dosages of statins on C-reactive protein (CRP) levels in patients with dyslipidemia or coronary heart disease. Methods: Randomized controlled trials were searched from PubMed, Embase, Cochrane Library, OpenGray, and ClinicalTrials.gov. We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines for data extraction and synthesis. The pairwise meta-analysis compared statins and controls using a random-effects model, and a network meta-analysis compared the types and dosages of statins using the Bayesian random-effects model. The PROSPERO registration number is CRD42021242067. Results: The study included 37 randomized controlled trials with 17,410 participants and 20 interventions. According to the pairwise meta-analysis, statins significantly decreased CRP levels compared to control (weighted mean difference [WMD] = -0.97, 95% confidence interval [CI] [-1.31, -0.64], P < 0.0001). In the network meta-analysis, simvastatin 40 mg/d appeared to be the best strategy for lowering CRP (Rank P = 0.18, WMD = -4.07, 95% CI = [-6.52, -1.77]). The same was true for the high-sensitivity CRP, non-acute coronary syndrome (ACS), < 12 months duration, and clear measurement subgroups. In the CRP subgroup (rank P = 0.79, WMD = -1.23, 95% CI = [-2.48, -0.08]) and ≥12-month duration subgroup (Rank P = 0.40, WMD = -2.13, 95% CI = [-4.24, -0.13]), atorvastatin 80 mg/d was most likely to be the best. There were no significant differences in the dyslipidemia and ACS subgroups (P > 0.05). Node-splitting analysis showed no significant inconsistency (P > 0.05) except for the coronary heart disease subgroup. Conclusions: Statins reduced serum CRP levels in patients with dyslipidemia or coronary heart disease. Simvastatin 40 mg/d might be the most effective therapy, and atorvastatin 80 mg/d showed the best long-term effect. This study provides a reference for choosing statin therapy based on LDL-C and CRP levels.